Whatever Happened to Projective Architecture? Rethinking the Expertise of the Architect - Lara Schrijver (Footprint)
This review article takes the discussion of ‘projective’ architecture as its starting point, and proposes that this recent debate may still be worthwhile to rethink the relationship between practice and theory in architecture. The spirit of ‘projective’ architecture suggests that we rethink how architecture ‘works’. This would entail understanding the reconfigured relation between political/societal and aesthetic/cultural engagement. Drawing from the ideas in the American debate on the ‘projective’ and the recent work of Richard Sennett on ‘craft’, this article puts forward the position that the notion of the ‘projective’ can extend the insights of critical theory towards a more fruitful dialogue with the everyday practice of architecture.